The Theology and History of the Exodus: The State of the Question - Longman III, Tremper (Buried History: The Journal of the Australian Institute of Archaeology, 2008)
The archaeological record as we currently understand it does not confirm the circumstances and date for the Exodus of the Israelites from Egypt. Indeed it does not unequivocally indicate that it happened at all. It is argued that while it may not matter that the precise details of the event are unknown to us, it is important to accept that the event did actually happen.